2014
DOI: 10.1074/jbc.m114.551366
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Tyrosine Phosphorylation of Protein Kinase Cδ (PKCδ) Protects the Salivary Gland from Radiation Damage

Abstract: Background: Nuclear import of protein kinase C␦ is required for DNA-damage-induced apoptosis. Results: c-Src and c-Abl phosphorylate PKC␦ to regulate nuclear import. Tyrosine kinase inhibitors block nuclear translocation of PKC␦ and suppress apoptosis. Conclusion: Tyrosine kinase inhibitors can regulate the pro-apoptotic function of protein kinase C␦. Significance: Tyrosine kinase inhibitors may improve the quality of life in cancer patients receiving radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 48 publications
2
39
0
1
Order By: Relevance
“…Our studies support a model whereby nuclear translocation of PKCδ is initiated by tyrosine phosphorylation at Y155 and Y164 by Abl and Src tyrosine kinases, respectively, resulting in a conformational change that facilitates importin-α binding and nuclear import (see Fig. 2, arrows 4, 5, and 6) (Adwan et al, 2011; Wie, Adwan, DeGregori, Anderson, & Reyland, 2014). The sequential phosphorylation of PKCδ by Abl and Src is likely to be critical to cellular homeostasis as it assures that pro-apoptotic signaling by PKCδ is linked to activation of other cell death signals.…”
Section: Biological Functions Of Pkcδsupporting
confidence: 85%
See 1 more Smart Citation
“…Our studies support a model whereby nuclear translocation of PKCδ is initiated by tyrosine phosphorylation at Y155 and Y164 by Abl and Src tyrosine kinases, respectively, resulting in a conformational change that facilitates importin-α binding and nuclear import (see Fig. 2, arrows 4, 5, and 6) (Adwan et al, 2011; Wie, Adwan, DeGregori, Anderson, & Reyland, 2014). The sequential phosphorylation of PKCδ by Abl and Src is likely to be critical to cellular homeostasis as it assures that pro-apoptotic signaling by PKCδ is linked to activation of other cell death signals.…”
Section: Biological Functions Of Pkcδsupporting
confidence: 85%
“…We show that phosphorylation of PKCδ at Y64 and Y155, nuclear accumulation of PKCδ, and apoptosis can be specifically inhibited by pre-treatment with tyrosine kinase inhibitors such as dasatinib and imatinib (Wie et al, 2014). Importantly, suppression of apoptosis in mice treated with irradiation to the head and neck is coupled with protection of salivary function in vivo (Wie and Reyland, unpublished data).…”
Section: Targeting Pkcδmentioning
confidence: 93%
“…PKCδ is involved in numerous cellular functions, including apoptosis, cell survival, migration and proliferation (Wie et al, 2014). The unique capability of PKCδ to regulate numerous cellular functions is attributed, at least in part, to its differential subcellular localization, especially stimulus-dependent organelle translocation.…”
Section: Discussionmentioning
confidence: 99%
“…6), suggesting that beneficial effects of the peptide are related to biochemical inhibition of this PKCd activation mechanism. Nuclear translocation of PKCd is critical for the initiation of cytotoxic or proapoptotic signaling (Humphries et al, 2008;Pabla et al, 2011), and inhibition of PKCd nuclear translocation was reported to be cytoprotective following ischemia-reperfusion (Kostyak et al, 2006), focal cerebral ischemia (Shimohata et al, 2007), and radiation damage (Wie et al, 2014). Nuclear translocation is required for cleavage of PKCd, which may increase PKCd activity by removal of the regulatory domain (Okhrimenko et al, 2005).…”
Section: Discussionmentioning
confidence: 99%